THERAPY-RELATED MYELOID NEOPLASMS IN PATIENTS TREATED FOR HODGKIN LYMPHOMA - Dennis A Eichenauer; Andreas Engert (Mediterranean Journal of Hematology and Infectious Diseases, 2011)
Hodgkin lymphoma (HL) is a malignancy of the lymphatic system with an incidence of 2-3/100.000/year in developed countries. With modern multi-agent chemotherapy protocols optionally combined with radiotherapy (RT), 80% to 90% of HL patients achieve long-term remission and can be considered cured. However, current standard approaches bear a considerable risk for the development of treatment-related late effects. Thus, one major focus of current clinical research in HL is reducing the incidence of these late effects that include heart failure, infertility, chronic fatigue and secondary malignancies such as secondary myelodysplastic syndrome and acute myeloid leukemia (secondary MDS/AML). In previous analyses, secondary MDS/AML after treatment for HL was associated with a poor prognosis. Nearly all patients died rapidly after diagnosis. However, more recent analyses indicated an improved outcome among patients with secondary MDS/AML who are eligible for modern anti-leukemic treatment and allogeneic stem cell transplantation (aSCT). This article gives an overview of recent reports on the incidence and the treatment of secondary MDS/AML after HL treatment and describes the efforts currently made to reduce the risk to develop this severe late effect.